UJI DAYA HAMBAT REBUSAN TANAMAN MENIRAN (Phyllanthus niruri L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli DENGAN METODE DIFUSI AGAR - Aulia Debby Pelu; Cut Bidara Panita Umar; Nahdiyanti Ias (Jurnal Kesehatan Amanah, 2021)
Meniran ( Phyllanthus niruri L.) is one of the plants used by the community for treatment. this plants is believed to have properties to treat diseases, one of which is the treatment of diarrhea. Porpose : This study was to identify the chemical content of meniran ( Phyllanthus niruri L.) stew, to determine the inhibition of the growht of Escherichia coli bacteria from each concenration of meniran (Phyllanthus niruri L.) stew. Methods :This study used an experimental desigh with concentration of 20%, 40%, 80% and 100%. Results : This study showed that meniran stew had chemical compounds, namely alkaloids, tannins and saponins that functioned as antibacterials and meniran ( Phyllanthus niruri L.) stew had antibacterial inhibition againts Escherichia coli bacteria at a concentration of 40% with a length of 15 mm in diameter. 80% diameter of inhibition 20 mm and 100% have a diameter of 24 mm in inhibition. for positive cotrol has a resistance of 30 mm and a negative control control of 0 mm.